Strategi Pemasaran Digital Busana Muslim di saat Pandemi Covid 19 - Hasna Aulia; Indri Rachmawati (UNISBA Press, 2022)
Abstract. The times have made marketing more sophisticated so that the emergence of digital marketing through e-commerce is one of them Shopee. Elzatta has joined Shopee for 5 years, from the assessment and appearance on e-commerce Shopee Elzatta is more attractive than other brands. This research was conducted so that the discussion focused on how digital marketing through e-commerce Shopee Elzatta during the covid-19 pandemic in maintaining sales and promoting products. The purpose of this research is to find out Elzatta uses digital marketing through Shopee e-commerce, to find out Elzatta's obstacles that occur in promoting products through Shopee e-commerce during the covid-19 pandemic, and to find out Elzatta's strategy in promoting products through e-commerce. Shopee during the covid-19 pandemic. In this study, the researcher uses the constructivist paradigm and uses a qualitative method with a case study approach. The technique of collecting data in this research is by observation and interviews. Informants in this study were Sales digital marketing Elzatta and Admin Shopee Elzatta. The data validity test in this study was source triangulation because it involved two informants. The results of this study are Elzatta uses Shopee e-commerce as a medium to carry out digital marketing activities because Shopee e-commerce is the platform most widely used by the public for online shopping which features free shipping, discounts and so on. Elzatta has experienced obstacles in promoting its products, due to the implementation of restrictions on community activities which are commonly called (ppkm) with digital marketing through Shopee e-commerce experiencing quite an increase. The strategy carried out in digital marketing through Shopee Elzatta's e-commerce during the covid-19 pandemic is through preparation, planning, implementation, and evaluation. Elzatta also participates in promotional programs at Shopee such as monthly sales and uses ads, and there are also special products so that can increase traffic and good exposure. The solution taken by Elzatta in promoting digital marketing through Shopee e-commerce during the covid-19 pandemic is by participating in the Shopee promotion program and also because now it's PPKM so Elzatta is doing a PPKM promotion, the purpose of Elzatta's PPKM promotional program is